Grids, Clouds and Virtualization - Cafaro, Massimo; Aloisio, Giovanni (London: Springer, 2011)
This timely text/reference introduces the fundamental principles and techniques underlying grids, clouds and virtualization technologies, as well as reviewing the latest research and expected future developments in the field.
Includes bibliographical references and index.
rua 21/02/17
Loans
Keywords: Computational grids (Computer systems); Cloud computing; Virtual computer systems; software engineering; Computer Science